Urban green space visitation and mental health wellbeing during COVID-19 in Bangkok, Thailand - Arifwidodo, Sigit D.; Chandrasiri, Orana (Frontiers in Public Health, 2024)
Urban green spaces offer numerous benefits, and their role in supporting mental health, particularly during global crises such as the COVID-19 pandemic, is of growing interest to researchers and policymakers. This study explored the relationship between urban green space visitation and mental health well-being during the COVID-19 pandemic in Bangkok, Thailand. This cross-sectional study, conducted in Bangkok during the COVID-19 lockdown, used a telephone survey of 579 respondents. A logistic regression model was employed to examine the association between urban green space visitation and the WHO-5 mental health well-being score, considering various factors such as socioeconomic variables, healthy behaviors, and COVID-19-related experiences. The findings revealed a significant association between urban green space visitation during the lockdown and higher mental health well-being. Socioeconomic variables and healthy behaviors of respondents were also notably linked to higher WHO-5 mental health well-being scores. These findings collectively indicate that urban greenspace visitation serves as a crucial determinant of mental health and well-being, especially during the COVID-19 pandemic.